ELECTROCHEMICAL SENSOR FOR THE DETECTION OF HYDROQUINONE USING A CARBON PASTE ELECTRODE MODIFIED WITH MOLECULARLY IMPRINTED POLY(METHYL RED) (Lantanida Journal, 2025)
Hydroquinone is a toxic compound that is still found in illegal cosmetic products, so the development of sensitive sensors is needed. In this study, an electrochemical sensor based on carbon paste electrode modified with molecularly imprinted poly(methyl red) (CPE–MIP) was developed to detect hydroquinone. Electrode modification was carried out by electropolymerization of methyl red in the presence of hydroquinone using cyclic voltammetry at a potential range of −0.6 to +1.4 V for 15 cycles. The surface morphology was characterized by Scanning Electron Microscope (SEM), while the electrochemical performance was evaluated using Differential Pulse Voltammetry (DPV). Compared with unmodified CPE, CPE–MIP showed an increase in the oxidation peak current and a shift towards lower oxidation potentials. The sensor showed a linear response to hydroquinone concentrations ranging from 20 to 20,000 µM with a coefficient of determination (R²) of 0.9992, a sensitivity of 0.0018 µA µM⁻¹, a limit of detection of 6.43 µM (3.3σ/slope), and good repeatability with a %RSD of 1.07% (n = 30) using a single. These results indicate that the fabricated CPE–MIP sensor exhibits promising initial analytical performance for hydroquinone detection and provides a basis for further validation.